Understanding campus mobility - Koh, Anthony Yao Wei (Nanyang Technological University, 2020)
The University campus is where students spend most of their time during the university period. Campus mobility thus provides input on how the campus facilities are used and the interaction between students on campus. One pronounce technology that is widely deployed on campus is Wi-Fi. Using the Wi-Fi data, we can explore the mobility of the student population, their interaction with facilities and each other. With the internationalisation of universities, there are more students who are participating in oversea exchange programs. In this project, we make us of the campus Wi-Fi log data captured over three semesters to look at the following: - General mobility patterns — In this study, we analyse the mobility pattern of users and the potential temporal and spatial motivations for the movement. - User mobility in a group setting — We discover hotspots where the potential spread of diseases could take place due to high human interaction. - Difference in mobility between local and exchange students — We found that exchange students are underutilising campus resources and there is a low correlation between the type of user (Local or Exchange) and whom they interact with. - How COVID-19 has affected the users on campus — Using statistical data, we found that there is a drop in the total number of students after the campus has reopened and the effectiveness of certain measures against COVID-19 The project has provided insights to the campus mobility pattern. We have also observed the impact of university and government policy due to COVID-19 on mobility pattern.